Diagnosis of Atelosteogenesis Type I suggested by Fetal Ultrasonography and Atypical Paternal Phenotype with Mosaicism - Meira, Joanna Goes Castro; Sarno, Manoel Alfredo Curvelo; Faria, Ágatha Cristhina Oliveira; Yamamoto, Guilherme Lopes; Bertola, Débora Romeo; Scheibler, Gabriela Gayer; Tavares, Dione Fernandes; Acosta, Angelina Xavier (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Atelosteogenesis type I (AOI) is an autosomal dominant skeletal dysplasia caused by mutations in the filaminB (FLNB) gene with classic and well-recognizable clinical findings. However, parents affected with a mild phenotype, probably with somatic mosaicism, can generate offspring with a much more severe phenotype of AOI. In the present report, we describe a female newborn with classic AOI leading to early neonatal death, whose diagnostic was based on prenatal radiological findings and on the physical examination of the father. Since her father had limb deformities and corporal asymmetry, suggesting somatic mosaicism, his biological samples were analyzed through a gene panel for skeletal dysplasias. A missense mutation not previously described in the literature was detected in the FLNB gene, affecting ∼ 20% of the evaluated cells and, therefore, confirming the diagnosis of mosaic AOI in the father. The molecular analysis of the father was crucial to suggest the diagnosis of AOI in the newborn, since she died early and there were no biological samples available.
Keywords: atelosteogenesis; somatic mosaicism; skeletal dysplasia; FLNB; exome-target sequencing; fetal ultrasonography